Analisis Strategi Pemasaran Makanan Tradisional (Studi Kasus Industri Rengginang di Kecamatan Sakra Pusat) - Susilawati Susilawati; Saeful Hakkul Yakin (Universitas Hamzanwadi, 2017)
This study aims to determine: 1). How is the implementation of a marketing strategy that has been applied by the industry rengginang players in the Sakra Center district, 2). Any internal and external factors that affect the marketing strategy at industrial rengginang in the Sakra Central District, 3). Alternative marketing strategies such as what is selected by the perpetrators of industrial enterprises rengginang in the Sakra Center district. The research method using a mix of methods.The nature of this research is comparative to come up with new in marketing strategies rengginang in the Sakra Centre District. Data collection instruments using questionnaires. Questionnaire data were analyzed using matrix IFE (2,380), EFE matrix (2.943), IE matrix (0.291 and 0, 288). SWOT analysis produced 8 alternative strategies that can be selected by the company are: 1) Maintain the price and improve product quality to increase customer satisfaction and loyalty. 2) Engaging with potential distributor agents to increase market share. 3) Utilize strategic locations to attract potential customers. 4) Create a product with the form and a new taste. 5) carry out the management system of the company's internal organization. 6) Build or rent a kiosk at strategic places to increase sales. 7) Conducting promotional activities and advertising to attract potential customers and expand the marketing area. 8) Build and develop joint ventures (Joint Venture) with those who provide capital and raw materials to increase production capacity.The results of matrix analysis QSPM, from eight strategic alternatives that exist, there is one alternative strategy that prioritized to be done by the company is maintaining prices and improve product quality to increase customer satisfaction and loyalty with TAS score of 6.445.